Black hole astrophysics 2002 : proceedings of the Sixth APCTP Winter School, Pohang, Korea, 9-12 January 2002 - Lee, Hyun Kyu; Park, Myeong-Gu (World Scientific, 2002)
This book consists of about 20 lectures on theoretical and observational aspects of astrophysical black holes, by experts in the field. The basic principles and astrophysical applications of the black hole magnetosphere and the Blandford-Znajek process are reviewed in detail, as well as accretion by black holes, black hole X-Ray binaries, black holes with cosmic strings, and so on. Recent advances in X-Ray observations of galactic black holes and new understanding of supermassive black holes in AGNs and normal galaxies are also discussed.